Contribution of Arm Muscle Strength and Eye-Hand Coordination Towards Volleyball Passing Ability of Physical Education Students - Rifqi, Muhamad; Kamarudin, Kamarudin; Alpen, Joni; Yulianti, Mimi (Indonesian Journal of Sport Management, 2025)
The purpose of this study was to determine the contribution of arm muscle strength and eye-hand coordination to the ability of underhand passing of Physical Education students in the 2024/2025 Academic Year of the Islamic University of Riau. This type of research is a multiple correlation study. The population and sample in this study were 14 male students of class 2F Physical Education at the Islamic University of Riau. The data collection instruments used in this study were arm muscle strength tests, eye-hand coordination tests, and volleyball underhand passing ability tests. Based on the results of the research that has been carried out, the conclusions in this study are: (1) There is a contribution of arm muscle strength to the results of underhand passing of physical education students with a contribution of 8.64%. (2) There is a contribution of eye-hand coordination to the results of underhand passing of physical education students with a contribution of 9.96%. (3) There is a contribution of arm muscle strength and eye-hand coordination to the results of underhand passing of physical education students with a contribution of 16.48%.